2005
DOI: 10.1186/1472-6920-5-38
|View full text |Cite
|
Sign up to set email alerts
|

Unhappiness and dissatisfaction in doctors cannot be predicted by selectors from medical school application forms: A prospective, longitudinal study

Abstract: BackgroundPersonal statements and referees' reports are widely used on medical school application forms, particularly in the UK, to assess the suitability of candidates for a career in medicine. However there are few studies which assess the validity of such information for predicting unhappiness or dissatisfaction with a career in medicine. Here we combine data from a long-term prospective study of medical student selection and training, with an experimental approach in which a large number of assessors used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…These studies also indicated that fellowship participants were more interested in non-clinical matters, such as research, teaching and leadership. This may be indicative of the general views espoused by other researchers on the role of a wider or more cosmopolitan view on the well-being of individuals 12 13…”
Section: Introductionmentioning
confidence: 76%
“…These studies also indicated that fellowship participants were more interested in non-clinical matters, such as research, teaching and leadership. This may be indicative of the general views espoused by other researchers on the role of a wider or more cosmopolitan view on the well-being of individuals 12 13…”
Section: Introductionmentioning
confidence: 76%
“…The predictive value of aptitude tests is uncertain. On the one hand, a review of prospective studies in the UK found that A level grades, but not aptitude tests, predicted performance in medical school examinations and part 1 of a postgraduate examination (McManus et al 2005a;McManus et al 2003). On the other hand, the scores obtained on the Medical College Admission Test (MCAT) have been reported to predict the performance on the USMLE step I (Donnon et al 2007) and on the Canadian Licensing Examinations-part II (communication and problem exploration skills) (Kulatunga-Moruzi and Norman 2002b), and regression analyses have indicated that the GPA and the MCAT scores had an independent predictive validity for medical school grades and USMLE scores (Julian 2005) (Table 1).…”
Section: Validitymentioning
confidence: 98%
“…These tests are expected to be fair, transparent, evidence-based and legally defensible (McManus et al 2005a). Their predictive value is determined not only by their reliability and validity, but also by the ''pre-test'' or ''prior'' probability of the non-cognitive trait under consideration, i.e., its prevalence in the population to which the tested individual belongs (Galen and Gambino 1975).…”
Section: Uncertainties In the Selection Of Applicants For Medical Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the overall evidence on most other predictors (often termed 'non-cognitive' predictors) is comparatively scarce 5 and even less convincing. 3,8,[10][11][12][13][14] The admission interview is widely used in medical education 15 and it is probably the best examined of the non-cognitive selection tools. 10 While the admission interview appears to have at least high 'face validity' for testing non-cognitive skills, such as communication skills and interpersonal skills, its reliability is controversial in health science education.…”
Section: Reliability In Admissionmentioning
confidence: 99%